Agency, futurity and representation: Conceptualising hope in recent sociological work. Issue 5 (September 2019) - Cook, Julia; Cuervo, Hernán
Although humanities and social science disciplines have witnessed an explosion of interest in the topic of hope in recent decades, uptake of this concept has been comparatively uneven in sociological research. Hope has garnered substantial attention in relation to topics such as health, poverty, youth and work within creative industries, while attracting sporadic interest elsewhere. However, despite this uneven engagement, studies addressing hope in each area have echoed many of the same ambiguities. We focus on two such ambiguities: the relationship between hope and futurity, and the relationship between hope and agency. Drawing on the observation that recent treatments of hope appear to either emphasise a hoped-for outcome situated in the future or focus on the role of hope in coping with the present we reframe this debate, contending that these tendencies suggest two distinct modes of hope: representational and non-representational. By reframing the relationship between hope and futurity thus we seek to, in turn, untangle the ambiguous relationship between hope and agency. We test the utility of our conceptualisations of hope by placing them into dialogue with longitudinal case studies compiled from biennial interviews and annual surveys conducted over a 10-year period. We ultimately put forward some means by which recent sociological treatments of hope can be unified, and in so doing contend that conceptualising hope not as an individual experience, but as part of broader political economies of hope can attune us to the ways in which inequalities are manifest through uneven distributions and experiences of hope.